Penyelesaian Sengketa Pembagian Waris Antar Anak yang di Selesaikan dengan Musyawarah - Ajeng Lestyarindi; Sri Astutik; Nur Handayati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the resolution of disputes over the division of inheritance between children carried out through deliberation and to analyze and identify the resolution of disputes over the division of inheritance between children carried out through deliberation. This research is included in the type of empirical legal research which is also known as empirical legal research or empirical legal research. The results of this research can be imperative or formal. Non-doctrinal research on law can produce new theories regarding the results of this research can be imperative or formal. Non-doctrinal research on law can produce new theories regarding the existence and function of law in society, as well as changes that may occur in the process of social change.The results of the research are the deliberation process in dividing inheritance through 3 stages or steps. First stage: Settlement of inheritance disputes is carried out internally between the heirs through family deliberations; Second stage: If the family deliberation does not reach an agreement, the deliberation leader can bring the dispute to the Head of the Hamlet or village government; Third stage: If the deliberation led by the village head does not produce an agreement or decision, the dispute is returned to the heirs to determine the next step. The success of the deliberation process is influenced by internal factors, such as openness and good intentions of the disputing parties, as well as external factors, such as the presence of a mediator and support from the social environment.